Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up